2020
DOI: 10.1016/j.eist.2019.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Modernization of Russian district heating systems with the help of biomass energy – A Gordian knot?

Abstract: The article discusses the prospects of local wood waste resources as replacements for fossil fuel imports in the remote settlements of the Russian North from a viewpoint of a case study: the Arkhangelsk region and its outdated heating and fossil fuel delivery systems. Drawing on energy transition literature and expert interviews, the most influential factors are defined in geographic-infrastructural, institutional, financial, and behavioral contexts. In conclusion, the article determines that a key issue is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…It is remarkably exhaustive, supplying both buildings and industry, but at the same time it is characteristically inefficient. Russian boiler efficiency is around 75% (while the European and American average is 85-90%), and the state has estimated that 30% of the system's infrastructure is in urgent need of repairs (41). The district heating system is fueled mostly by gas (66%) and coal products (21%) (42).…”
Section: Policy Environment Surrounding District Heating Modernization and Renewablesmentioning
confidence: 99%
See 3 more Smart Citations
“…It is remarkably exhaustive, supplying both buildings and industry, but at the same time it is characteristically inefficient. Russian boiler efficiency is around 75% (while the European and American average is 85-90%), and the state has estimated that 30% of the system's infrastructure is in urgent need of repairs (41). The district heating system is fueled mostly by gas (66%) and coal products (21%) (42).…”
Section: Policy Environment Surrounding District Heating Modernization and Renewablesmentioning
confidence: 99%
“…Local newspapers have revealed that the winter coal reserves have been insufficient and around half of the boilers of local power plants not suitable for winter use (1,2). As a result of these problems, the price of heat, which has already experienced several price hikes in the 2010s, is at risk of increasing more, especially for far-flung settlements (3,4). The issue of ensuring heat supply considers several sectors of the society due to the deep structural problems involved, such as the high wear and obsolescence of heating infrastructure, the long distances, and short transport seasons (5).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research also suggests that the aging fossil fuel energy infrastructure and the high cost of acquiring diesel constitute powerful drivers for remote communities to establish small-scale wind, solar or hybrid (wind-diesel, solar-diesel) utilities to supplement diesel generators (Mortensen et al, 2017). In Russia, municipalities are legally obligated to take responsibility for the local energy and utilities, yet, the local realities vary due to different infrastructure (Salonen, 2019). In order to reflect this fact, we introduce utility spending as an indicator measuring the share of housing and utilities spending from the total municipal income.…”
Section: Efa: Variables Description and Operationalisationmentioning
confidence: 99%